From a cycloheptatrienylzirconium allyl complex to a cycloheptatrienylzirconium imidazolin-2-iminato "pogo stick" complex with imido-type reactivity - Glöckner, Andreas; Bannenberg, Thomas; Daniliuc, Constantin G; Jones, Peter G; Tamm, Matthias (Inorganic chemistry, 2012)
The reaction of the cycloheptatrienylzirconium half-sandwich complex [(η(7)-C(7)H(7))ZrCl(tmeda)] (1) (tmeda = N,N,N',N'-tetramethylethylenediamine) with Li(Im(Dipp)N), generated from bis(2,6-diisopropylphenyl)imidazolin-2-imine (Im(Dipp)NH) with methyllithium, yields the imidazolin-2-iminato complex [(η(7)-C(7)H(7))Zr(Im(Dipp)N)(tmeda)] (2). The corresponding tmeda-free complex [(η(7)-C(7)H(7))Zr(Im(Dipp)N)] (5) can be synthesized via the 1,3-bis(trimethylsilyl)allyl complex [(η(7)-C(7)H(7))Zr{η(3)-C(3)H(3)(TMS)(2)}(THF)] (3; TMS = SiMe(3)), which undergoes an acid-base reaction with Im(Dipp)NH to form 5 and 1,3-bis(trimethylsilyl)propene. 5 exhibits an unusual one-legged piano stool ("pogo stick") geometry with a particularly short Zr-N bond of 1.997(2) Å. Addition of 2,6-dimethylphenyl or tert-butyl isocyanide affords the complexes [(η(7)-C(7)H(7))Zr(Im(Dipp)N)(CNR)] (R = o-Xy, 6; R = t-Bu, 7), while the reaction with 2,6-dimethylphenyl isocyanate results in a [2 + 2] cycloaddition to form the ureato(1-) complex [(η(7)-C(7)H(7))Zr{Im(Dipp)N(C═O)N-o-Xy}] (8). 5 can also act as an initiator for the ring-opening polymerization of ε-caprolactone. These reactivity patterns together with density functional theory calculations reveal a marked similarity of the bonding in imidazolin-2-iminato and conventional imido transition-metal complexes.